2015
DOI: 10.3390/aerospace2020203
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Shock Wave Attenuation in Two-Dimensional Ducts Using Solid Obstacles: How to Utilize Shock Focusing Techniques to Attenuate Shock Waves

Abstract: Research on shock wave mitigation in channels has been a topic of much attention in the shock wave community. One approach to attenuate an incident shock wave is to use obstacles of various geometries arranged in different patterns. This work is inspired by the study from Chaudhuri et al. (2013), in which cylinders, squares and triangles placed in staggered and non-staggered subsequent columns were used to attenuate a planar incident shock wave. Here, we present numerical simulations using a different obstacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…As a result, Skews et al [7] suggested trapping shock wave in a duct with first rows of convergent obstacles followed by rows of divergent obstacles. By confirming the results of Chaudhuri et al [5], Wan et al [8] showed that the obstacles with circular section are not the most efficient to mitigate shock wave. However, obstacles with circular section represent a good approximation of actual environment in urban configuration (poles, trees, traffic lights, humans…).…”
Section: Introductionsupporting
confidence: 53%
“…As a result, Skews et al [7] suggested trapping shock wave in a duct with first rows of convergent obstacles followed by rows of divergent obstacles. By confirming the results of Chaudhuri et al [5], Wan et al [8] showed that the obstacles with circular section are not the most efficient to mitigate shock wave. However, obstacles with circular section represent a good approximation of actual environment in urban configuration (poles, trees, traffic lights, humans…).…”
Section: Introductionsupporting
confidence: 53%
“…The 3D simulation was conducted using Overture, which is an open-source object-oriented code framework to solve partial differential equations using finite differences on composite grids. More information regarding the solver and the method can be found at http://www.overtureframework.org/ or in our previous work [11]. In the simulation, cuboid elements are used to mesh the shock tube.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the shock wave literature reveals many studies investigating various methods of mitigation. Some methods that have proven effective for this purpose include the introduction of bends inside a duct [1,2], the addition of rigid or semi-rigid structures in the path of the shock wave and baffles, orifices, perforated plates with holes or slits, grids and obstacles of varying geometries placed in different patterns [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the staggered matrix of reversed triangular prisms most efficiently attenuated the incident shock wave. More recently, Wan and Eliasson (2015) numerically investigated the shock attenuation ability of a shock focusing geometry. Square and cylindrical rigid obstacles were equidistantly arranged along the edge of a logarithmic spiral, and fixed into a channel.…”
Section: Introductionmentioning
confidence: 99%